Does a Freeze-thaw Pretreatment Enhance the Quality of Dried Foods? A Meta-Analysis - Tri Yulni; Wendianing Putri Luketsi Luketsi; Waqif Agusta; Ermi Erene Koeslulat; Spetriani Spetriani; Lully Natharina Prasetyani (Jurnal Keteknikan Pertanian, 2023)
Based on the results of several studies, it's questionable if freeze-thaw pretreatment can improve dried product qualities. To answer this question, a meta-analysis was conducted to determine the effect of freeze-thaw pretreatment on the quality of dried products. This research aimed to assess the impact of freeze-thaw pretreatment on the quality of dried plant-based foods. The data was sourced from the Scopus database, and the selection criteria were based on the PRISMA protocol. All meta-analysis calculations were performed using OpenMEE Software. The results revealed that freeze-thaw pretreatment significantly affected ΔE, TFC, and TPC. However, freeze-thaw pretreatment does not significantly affect shrinkage and hardness. Based on what the analysis subgroup found, the best freezing temperatures are -20 °C and -196 °C because both temperatures favorably impact TFC and hardness. Moreover, freeze-thaw pretreatment is applicable to I-C, NIR, and HA-MV drying.